Topological asymptotic analysis of a diffusive–convective–reactive problem. Issue 1 (15th July 2020) - Ruscheinsky, Dirlei; Carvalho, Fernando; Anflor, Carla; Novotny, Andre Antonio
Abstract : Purpose: The purpose of this study is sensitivity analysis of the L 2 -norm and H 1 -seminorm of the solution of a diffusive–convective–reactive problem to topological changes of the underlying material. Design/methodology/approach: The topological derivative method is used to devise a simple and efficient topology design algorithm based on a level-set domain representation method. Findings: Remarkably simple analytical expressions for the sensitivities are derived, which are useful for practical applications including heat exchange topology design and membrane eigenvalue maximization. Originality/value: The topological asymptotic expansion associated with a diffusive–convective–reactive equation is rigorously derived, which is not available in the literature yet.